PENGARUH KEPAMIMPINAN VISIONER KEPALA SEKOLAH DAN KOMITMEN ORGANISASI TERHADAP KOMPETENSI PROFESIONAL GURU SMP NEGERI - Wahyuni, Apri; Hariri, Hasan; Rini, Riswanti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
This study employed an ex post facto quantitative approach to investigate the individual and combined effects of visionary leadership and organizational commitment of school principals on the professional competence of 144 randomly selected State Middle School teachers in Pesawaran Regency, out of a population of 225. Data was collected through questionnaires and analyzed using simple and multiple regression techniques after conducting prerequisite regression tests. The findings indicate that both the principal's visionary leadership and organizational commitment have a significant positive influence on enhancing teacher professional competence when examined individually. Moreover, when considered together, these factors collectively contribute significantly to the improvement of teacher professional competence.